New Therapeutic Targets for Mood Disorders - Rodrigo Machado-Vieira; Giacomo Salvadore; Nancy DiazGranados; Lobna Ibrahim; David Latov; Cristina Wheeler-Castillo; Jacqueline Baumann; Ioline D. Henter; Carlos A. Zarate (The Scientific World Journal)
Existing pharmacological treatments for bipolar disorder (BPD) and major depressive disorder (MDD) are often insufficient for many patients. Here we describe a number of targets/compounds that clinical and preclinical studies suggest could result in putative novel treatments for mood disorders. These include: (1) glycogen synthase kinase-3 (GSK-3) and protein kinase C (PKC), (2) the purinergic system, (3) histone deacetylases (HDACs), (4) the melatonergic system, (5) the tachykinin neuropeptides system, (6) the glutamatergic system, and (7) oxidative stress and bioenergetics. The paper reviews data on new compounds that have shown antimanic or antidepressant effects in subjects with mood disorders, or similar effects in preclinical animal models. Overall, an improved understanding of the neurobiological underpinnings of mood disorders is critical in order to develop targeted treatments that are more effective, act more rapidly, and are better tolerated than currently available therapies.